How new media portrays our athletes / Nurfazira Julaihi…[et.al] - Julaihi, Nurfazira; Zakariah, Nuratikahtasnim; Razak, Nur Syafiqah; Ab Latif, Nurul Aqilah; Zolkiple, Zul Zhareff Danial; Wan Abdul Aziz, Wan Abdul Muiz (Faculty of Communication and Media Studies, 2016)
This research paper is mainly about the new media and athletes. Our topic is "How New Media Portrays our Athletes". The purpose of conducting this research paper is to study on how media portray our athlete, to determine whether the media choosing to gain more profit than pride of our athlete especially in Malaysia. All data collected to support this research is from a method called in-depth interview and unit of analysis is by individuals. Data were analyzed using thematic analysis. We have interviewed few experts such as to Ilya Kareena Abdeen Binti Ibrahim, UiTM Althetes on squash Muhammad Aliff Bin Nordin, football athletes of UiTM, Nazirul Hadi Bin Norjali, futsal athlete, Nor Amirul Syaffiq Bin Khairul Annuar, Silat athletes, Nurizzatul Nabila Binti Zakaria, hockey players, Mr. Ishak journalist chief of Melaka Hari Ini and Puan Rozana Sani, a reporter from New Strait Times (NST) to participate in our interview. From the interview we have found that, most of informants have come to an agreement that the factors and impacts of new social media addiction are generally to get attention, and impacting one's social skills development.